Significance of transvaginal sonographic assessment of cervical length before induction of labour - M. S., Shreya; C., Savitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The traditional method of predicting whether an induced labor will result in successful vaginal delivery is based on pre-induction favourability of cervix as assessed by bishop score. However, this method is limited by subjectivity and reproducibility and though done in all the patients prior to induction of labour, several studies have demonstrated poor correlation between Bishop score and outcome of labor. Currently assessment of cervical status by sonographically at term in induction of labor is most accurate and highly reproducible compared to Bishop score. Methods: This study was carried out in a tertiary care teaching institute in Karnataka. 180 pregnant women at or beyond 37weeks who were planned for induction, Bishop score assessment of cervix and cervical assessment by ultrasound such as cervical length (CL) was done one day prior to induction. Induction was with 0.5mg PGE2gel. Maximum 3 induction were carried out over a period of 24hrs. Primary outcome of the study was the onset of active labor. Results: Amongst 160 pregnant women who were induced (20 women were excluded has they underwent LSCS for some other reasons during latent phase) cervical length by sonography <2cm were 14 none had failed induction. Amongst 180 pregnant women who were induced cervical length <2cm in 14 all had Bishop score >4. Conclusions: Transvaginal sonographic measurement of cervical length was evaluated in predicting response to induction. CL <2cm was associated with greater incidence of successful labor induction. These results show the CL has significant role in predicting outcome of labor.